Lack of an association between the aPKCλ/ι expression in prostate cancer and the patient outcomes. (2017) - Yokomizo, Yumiko; Kawahara, Takashi; Nagashima, Yoji; Ishiguro, Hitoshi; Kato, Ikuma; Yao, Masahiro; Miyamoto, Hiroshi; Uemura, Hiroji
Highlights: This is the first study to assess aPKCλ/ι expression in primary prostate cancer with metastatic disease. A total of 43 patients with prostate cancer and its metastasis to the lymph node and/or bone were analyzed in this study. We found no strong association between aPKCλ/ι expression and the prognosis of the patients.